Extraction and characterization of spherical nanocellulose from sesame husks - Mohammed Al-haql; Hoda Habbal; Bassam Al Oklah; Nesreen Qurabi (Heliyon)
The objective of this study was to extract and characterize nanocellulose from sesame husks, which are typically discarded as waste by sesame processing facilities. However, these husks are rich in cellulose, presenting a valuable potential source for nanocellulose. Sesame husk cellulose (SHC) was initially isolated through a multi-step process that removed oil, hemicellulose, and lignin. Sesame husk nanocellulose (SHNC) was subsequently obtained via acid hydrolysis. Energy-dispersive X-ray (EDX) analysis revealed a purity of 99.32 % for SHNC. The yields of SHC and SHNC were 25.16 % and 9.17 %, respectively. SHNC exhibited a lower surface charge (−27.2 mV) compared to SHC (−15.5 mV). FTIR confirmed the presence of characteristic cellulose bands. Dynamic light scattering (DLS) revealed average particle diameters of 2235 nm for SHC and 108.1 nm for SHNC. Atomic force microscopy (AFM) and field-emission scanning electron microscopy (FE-SEM) analyses showed that SHNC particles were spherical to oval-shaped, with average diameters of 78.41 nm and 74.30 nm, respectively. The crystallinity index was higher for SHNC (67.74 %) compared to SHC (41.02 %). Thermogravimetric analysis (TGA) indicated greater thermal stability for SHC (TMax 317 °C) compared to SHNC (TMax 287 °C). These results demonstrate the potential of sesame husks as a sustainable and valuable source of nanocellulose.